Comparative Study on Voice Based Chat Bots - Anusha, S; Karthik, N Vignesh; Sampada, KS (International Journal of Computer Sciences and Engineering, 2018)
Natural dialog conversation between humans and machines is a flourishing topic of the modern world, now show off their presence across a range of daily use devices and digital assistants. This is tried to be achieved by using sub-field of Artificial Intelligence named Natural Language Processing. The task is to be practically implemented through a series of convenient and capable categories by some of the market leaders with their successful products named the Amazon ALEXA, Microsoft CORTANA, Google ASSISTANT, Apple SIRI to quote a few. A virtual assistant put to real world usage has to perfectly emulate a human dialogue, analyze the input given by a user, represent the same correctly, convert to its process able form and formulate a relevant and appropriate response. In this paper, we review a few market leading voice based chat bots, identifying their technical aspects along with their advantages and disadvantages during the practical usage.